METHOD FOR ANALYSING MOTOR VEHICLES’ ENERGY EFFICIENCY AND THEIR TECHNICAL PARAMETERS CHANGES TO CONSIDER - Хмельов, Ігор; Гальона, Інеса; Даниленко, Інна; Довбій, Валентина; Мнишенко, Роман (SWorldJournal, 2024)
The paper considers the existing indicators for assessing the efficiency of vehicles, which are based on the calculated schemes of cargo delivery and which consider vehicles as self-propelled bodies and their virtual movement, and, therefore, they allow